How Do People React to Income-Based Fines? Evidence from Speeding Tickets Discontinuities - Kaila, Martti (Review of Economic Studies, 2026)
This article studies the impact of income-based criminal punishments on crime. In Finland, speeding tickets become income-dependent if the driver’s speed exceeds the speeding limit by more than 20 km/h, leading to a substantial jump in the size of the speeding ticket. Contrary to predictions of a traditional Becker model, individuals do not bunch below the fine hike. Instead, the speeding distributions are smooth at the cutoff. However, I demonstrate that the size of the realized speeding ticket has sizable, but short-lived, impacts on reoffending. I use a regression discontinuity design to show that fines that are, on average, 200 euros larger decrease reoffending by 15% in the following 6 months. The drop in reoffending is driven by high-income individuals facing the highest fine at the cutoff. I estimate that a fixed fine hike that matches the current deterrence effect would raise the fine increase faced by the bottom income quartile by about 300% at the cutoff, relative to the increase they face under the current income-based schedule. My empirical results are consistent with an explanation that people operate under information frictions. To illustrate this, I construct a Becker model with misperception and learning that can explain all the empirical findings.